2017
DOI: 10.1002/pits.22027
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Engagement and Disaffection in a Social Studies Classroom Context

Abstract: In this investigation, we replicated Skinner et al.'s study of the dynamics of engagement with a more diverse sample of Grades 6 and 7 students from a middle school with a large English learner (primarily Spanish-speaking) student population. We tested dimensions of the self-system model of motivational development in a specific academic domain (i.e., social studies). Some relationships found by Skinner and colleagues were supported, whereas others were not. Emotional engagement predicted changes in behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The high correlation between behavioural and cognitive engagement and emotional engagement prevented examination of the association between those two engagement dimensions. Barber, Buehl, and Beck (2017) found that high emotional engagement predicted high behavioural engagement, but not vice versa. It would be important to examine this topic in more depth with chronologically ordered data, as used in this study.…”
Section: Limitationsmentioning
confidence: 93%
“…The high correlation between behavioural and cognitive engagement and emotional engagement prevented examination of the association between those two engagement dimensions. Barber, Buehl, and Beck (2017) found that high emotional engagement predicted high behavioural engagement, but not vice versa. It would be important to examine this topic in more depth with chronologically ordered data, as used in this study.…”
Section: Limitationsmentioning
confidence: 93%
“…Even for EBs who are well on their path to developing English proficiency, reading in English at school may be anxiety‐inducing, as they may perceive themselves as weaker readers than their EM counterparts (whether they are or not), leading to lower self‐efficacy for reading in English, a key contributor to the low sense of control that contributes to anxiety development in the control–value theory (Pekrun, 2016). Although a few studies in the last decade have explored reading engagement and motivation in EBs (e.g., Taboada, Townsend, & Boynton, 2013; Taboada Barber et al, 2017; Taboada Barber, Klauda, & Stapleton, 2020), to date, no known studies have examined the extent to which EBs compare with other language groups in levels of anxiety specific to reading. In addition, no known studies have examined how reading anxiety relates to EBs’ reading engagement and achievement.…”
Section: Relations Of Reading Anxiety Engagement and Achievement In Ebs And Ems: Extant Researchmentioning
confidence: 99%
“…In EBs, the exploration of the various facets of reading engagement and their relations to reading achievement has been more limited but has taken several directions in the last decade. For example, studies have shown that teachers rate elementary‐grade EBs and EMs similarly in levels of reading engagement (Taboada Barber, Cartwright, et al, 2020; Taboada Barber, Klauda, & Stapleton, 2020) and that the dynamics and indicators of engagement are similar for EBs and their EM peers in the middle grades (e.g., Taboada Barber et al, 2017), with behavioral and cognitive engagement playing a strong role in predicting achievement in grade 6 students.…”
Section: Relations Of Reading Anxiety Engagement and Achievement In Ebs And Ems: Extant Researchmentioning
confidence: 99%
See 1 more Smart Citation